Health Education and Strengthening the Women's Awareness of Health - et. al., Hind Nadhim Kazar , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research attempted to answer a major question about what affects health education on the sources of knowledge of women in Iraqi society related to health issues? The research aims to identify the effect of health education on the sources of knowledge of women in Iraqi society related to health issues, and the importance of research is determined in knowing the effect of health education on the sources of knowledge of women in Iraqi society related to health issues. The past decades have witnessed a high change in the patterns of diseases and their spread among members of society, from infectious diseases to chronic diseases, especially diseases that are expressed in diseases of the lifestyle such as heart disease and diabetes, and many of these diseases are the result of wrong behavior, hence health education is the cornerstone of prevention. One of these diseases is the first health promotion stimulant, through which knowledge and information are raised, trends are built and health behaviors changed, and in recent years the concepts of health education have been elevated to become a knowledge science that uses behavioral and educational theories, methods of communication, means of education, and media principles to raise the health level of the individuals and society. Since health is a state of physical, psychological, mental, social and spiritual integration and not merely freedom from disease or disability, and health promotion is that science that helps individuals improve their lifestyles as well as enabling them to control and improve their health, and a healthy habit is what an individual does without thinking or feeling as a result Repeat it frequently.